2017
DOI: 10.1055/s-0037-1598310
|View full text |Cite
|
Sign up to set email alerts
|

Validity and usability of physical activity monitoring in patients with chronic obstructive pulmonary disease (COPD)

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 14 publications
(17 reference statements)
0
15
0
1
Order By: Relevance
“…The total sample includes 290 participants with a mean age of 70.2±4.8 years and females constitute 46.7±26.1% (Table 1). Studies were performed in Europe [14,16], Australia [11,13], UK [17], US [15] and Canada [12]. Of the samples, one recruited participants during hospitalisation yet the primary monitoring period was measured in a free-living environment [16], the remainder were community-dwelling adults.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
“…The total sample includes 290 participants with a mean age of 70.2±4.8 years and females constitute 46.7±26.1% (Table 1). Studies were performed in Europe [14,16], Australia [11,13], UK [17], US [15] and Canada [12]. Of the samples, one recruited participants during hospitalisation yet the primary monitoring period was measured in a free-living environment [16], the remainder were community-dwelling adults.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
“…Im Fokus der Bemühungen steht das Entgegenwirken der durch die Erkrankung hervorgerufenen physischen Dekonditionierung und der verminderten körperlichen Aktivität. Da die körperliche Aktivität mit dem Alter und dem COPD-Grad deutlich abzunehmen scheint, hat dieser Faktor eine hohe Bedeutung [1]. Ursächlich sind die zahlreichen biochemischen Veränderungen des Stoffwechsels für den Verlust der Muskulatur, vor allem der unteren Extremitäten [2].…”
Section: Introductionunclassified
“…The Polar A300 watch is an example of a commercially available activity tracker. This watch was validated in a study by Boeselt et al (2016). Within this study, Boeselt et al (2016) compared the Polar A300 to the previously validated Bodymedia-SenseWear activity tracker.…”
Section: Activity Trackermentioning
confidence: 99%
“…This watch was validated in a study by Boeselt et al (2016). Within this study, Boeselt et al (2016) compared the Polar A300 to the previously validated Bodymedia-SenseWear activity tracker. It was found that when compared using linear regression analysis and Bland-Altman plots, there were no significant differences between steps, calories burned, daily activity time, and metabolic equivalents (Boeselt et al, 2016).…”
Section: Activity Trackermentioning
confidence: 99%
See 1 more Smart Citation